PENGARUH TATA KELOLA RISIKO TERHADAP KINERJA BANK (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2015-2017) - Maghfira Dwi Puspita; Imam Ghozali (Diponegoro Journal of Accounting, 2019)
The aims of this study to discuss the relationship of risk governanceand bank performance. The independent variable in this research are level of risk disclosure, the number of risk committee, and the activity of risk committee.. While the dependent variable used in this study is ROA, ROE, and Tobin’s Q.This study uses secondary data from annually report of banking company listed on the Indonesia Stock Exchange. The population in this research is banking company listed on the BEI 2015-2017. The sampling method used is purposive sampling. Total sample of this research 106. This study uses multiple regression analysis to test the relationship between independent variable and dependent variable. The results showed that the level of risk disclosure has a positively related to bank performance, number of risk committee not influenced on bank performance, and activity of risk committee influenced on bank performance (ROE and Tobin’s Q).